If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -4.6 = 4y Reorder the terms: -4.6 + 3y = 4y Solving -4.6 + 3y = 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -4.6 + 3y + -4y = 4y + -4y Combine like terms: 3y + -4y = -1y -4.6 + -1y = 4y + -4y Combine like terms: 4y + -4y = 0 -4.6 + -1y = 0 Add '4.6' to each side of the equation. -4.6 + 4.6 + -1y = 0 + 4.6 Combine like terms: -4.6 + 4.6 = 0.0 0.0 + -1y = 0 + 4.6 -1y = 0 + 4.6 Combine like terms: 0 + 4.6 = 4.6 -1y = 4.6 Divide each side by '-1'. y = -4.6 Simplifying y = -4.6
| 4.4m+6.2=-8.8m-1.8 | | 4(5+b)=-12 | | x-12=5.2 | | 3y=12x-27 | | 3x+36-5=1+6v | | 7x^2+15x=18 | | 67=3.9r | | 3(2z-1)=4z-2 | | 29+3y=4.5+.5y | | 0.2x-3=-3.14 | | 4(5+b)=12 | | 16=f+12 | | -2.6(14-x)=15.6 | | 27a^3+18a^2=3a | | 76-2x=13-9x | | 10y-50=-150 | | x-3y=29 | | 50x^2=98 | | 5/9n-2=2/3n | | -14=-7x+2(6x-22) | | 2x=6.8 | | 7(6-3x)+2= | | 72=4.5n | | -4v-2v-16=38 | | lnx+ln(x+5)=ln(8x+10) | | -x-42=-3x+14 | | 5(-x+7)=20 | | 10-5(9n-9)=10-5 | | 6y-2=-3 | | 20y^2+9y-20=0 | | 04(1.5c+6)-2c=-9 | | x-20=60 |